Novel identities involving Genocchi numbers and polynomials arising from applications of umbral calculus - Araci, Serkan; Aracı, Serkan (ELSEVIER SCIENCE INC, 2014)
The aim of this paper is to deal with applications of umbral calculus on fermionic p-adic integral on Z(p). From those applications, we derive some new identities on Genocchi numbers and polynomials. Moreover, a systemic study of the class of Sheffer sequences on the generating function of Genocchi polynomials are given. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Appell sequence; Sheffer sequence; Genocchi numbers and polynomials; Formal power series; Fermionic p-adic integral on Z(p)